PENGATURAN PERLINDUNGAN HUKUM TERHADAP WISATAWAN - Novi Rahayu Widiastari, Ni Made; Sri Indrawati, A. A. (Kertha Semaya : Journal Ilmu Hukum, 2013)
This writing focuses on the study of law protection arrangement to ward tourist inaccordance to Indonesian constitution. The research presented in this writing is a normativeresearch based on secondary data (library data). The result of the research shows that eventhough it is still limited and needs describing more detail, law protection toward tourists hasbeen arranged in the constitutions both in the Undang-Undang Number 10 Year 2009 ontourism and the Undang-Undang Number 8 Year 1999 on Consumers Protection.
Keywords: Arrangement, Law Protection, Tourists